Review: Gambaran Permasalahan Obat Tidak Tercampurkan Pada Sediaan Semisolid (Krim, Gel, dan Salep) Serta Pengatasannya - Suhendi, Jessica Rianty; Saputra, I Putu Agus; Warditiani, Ni Kadek; Sari, Pande Made Nova Armita; Atuti, Ni Made Widi (Jurnal Farmasi Udayana; Vol. 13, No. 2, Tahun 2024, 2025)
Incompatibility refers to undesirable interactions between two or more drug substances that can lead to physical, chemical, or pharmacological changes. This incompatibility can affect pharmaceutical preparations' stability, effectiveness, and safety, including semi-solid formulations such as creams, gels, and ointments. This study aims to explore incompatibility in semi-solid preparations, particularly in the compounding process and its remedies based on existing research articles. The research was conducted by searching for journals in databases, selecting them based on established inclusion and exclusion criteria, and then interpreting the results from the chosen articles. The findings revealed 4 journals related to creams, 2 concerning gels, and 1 about ointments obtained from Google Scholar and PubMed for further analysis. The analysis indicated that incompatibility is often caused by differences in physicochemical properties between active substances and other components in the formulation, leading to phase separation and reduced drug efficacy. This issue can be mitigated by adding appropriate emulsifiers, paying attention to storage conditions, and conducting stability evaluations when necessary. This study emphasizes the importance of understanding incompatibility during the mixing and compounding of drugs to prevent potential issues that could compromise drug efficacy and patient safety.